(untitled) - Farhan Arifin (Universitas Ahmad Dahlan, 2022)
The motivation of L2 learners, which has been the focus of many research studies in second/foreign language acquisition, is one of the most important educational variables identified so far in the field. Besides motivation problems may arise as a result of personal issues as well as other factors such as gender, age, or other demographic differences. However, few people discuss the impact of demographic characteristics on learners' motivation, despite the fact that motivation is crucial in achieving good learning outcomes. The researcher wanted to explore the role of demographic characteristics on Indonesian high school students' L2MSS to learn English based on gender, parents' educational b